2022
DOI: 10.1038/s41598-022-09278-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and antitumor activity of a mutant type of interleukin 2

Abstract: Interleukin-2 (IL-2) is an important cytokine in survival, expansion, function of CD8+ T cells and natural killer cells in immunotherapy of melanoma and renal cell carcinomas. Its severe toxicity following binding to its high affinity IL-2 receptor alpha (IL-2Rα) has restricted its application in cancer patients. In the present study, we investigated the antitumor efficacy and cytotoxicity of a mutated human IL-2 previously designed by selective amino acid substitutions, and its reduced affinity towards high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Therefore, the induced proliferation of UF could be due to the overwhelming influence of excess sodium ions obtained through diets on IL-2. A mutant IL-2 was implicated in inhibiting the progression of a similar tumour, which gives credence to the postulated role of IL-2 in the growth of UF in this study [68]. The influence of the interaction of IL-2 with either zinc, vitamins B1, D, or particularly vitamin A that was implicated in the propagation of UF in this study was reported [69][70][71][72][73].…”
Section: Inflammatory Cytokines In Ufsupporting
confidence: 77%
“…Therefore, the induced proliferation of UF could be due to the overwhelming influence of excess sodium ions obtained through diets on IL-2. A mutant IL-2 was implicated in inhibiting the progression of a similar tumour, which gives credence to the postulated role of IL-2 in the growth of UF in this study [68]. The influence of the interaction of IL-2 with either zinc, vitamins B1, D, or particularly vitamin A that was implicated in the propagation of UF in this study was reported [69][70][71][72][73].…”
Section: Inflammatory Cytokines In Ufsupporting
confidence: 77%
“…The FDA approved the use of high-dose interleukin-2 (IL-2) therapy in 1992 for metastatic renal cell carcinoma and in 1998 for the treatment of metastatic melanoma ( 46 ). A different meta-analysis demonstrates that IL-2 combination medication effectively cures non-small cell lung cancer (NSCLC), increases overall survival, and has few harmful side effects ( 47 ). In individuals with advanced NSCLC, IL-2 serum level determination by regression analysis was demonstrated to have independent predictive value; as a result, its potential application for outcome prediction is advocated ( 48 ).…”
Section: Serum Cytokine Levels As Possible Immunotherapeutic Targetsmentioning
confidence: 99%